Transport of Microplastics From the Daugava Estuary to the Open Sea - Frishfelds, Vilnis; Murawski, Jens; She, Jun (Frontiers in Marine Science, 2022)
This study considers the transport of microplastics (MPs) from inland waters (rivers and lakes) to coastal waters and then to the open sea. A three-dimensional MP Eulerian tracer model based on the HIROMB-BOOS model (HBM) with wave-induced transport and biofouling process is used. Multilayer two-way nested model grids with 3–0.5–0.25–0.05 nautical mile resolutions are applied to resolve relevant riverine–estuarial–coastal hydrodynamics with a focus on the southern waters in the Gulf of Riga. The major river of the Gulf of Riga, Daugava, is governed by the Riga Hydro Power Station (RHPS) with high daily and weekly variability of the runoff creating more intense outflows during its working hours. This gives additional complexity when calibrating this model. The model results are validated against MP observations that are collected on various cruises in the summer of 2018 in the Gulf of Riga. There exists a strong synoptic variability in the observations, which are also reproduced. As the rivers are the primary source of MPs, a special backtracking algorithm was developed to find the most possible source of pollutants at a given location and time. The backtracking algorithm includes optimization with respect to salinity in order to prefer trajectories coming from freshwater and, consequently, MP sources. Lagrangian drift studies are performed for events with high precipitation in the estuary domain when sewer overflow at wastewater treatment plants (WWTPs) can occur, and the results are compared with different MP components in observations.